2014
DOI: 10.3390/nano4020203
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Potential Impact of Multi-Walled Carbon Nanotubes Exposure to the Seedling Stage of Selected Plant Species

Abstract: Phytotoxicity is a significant consideration in understanding the potential environmental impact of nanoparticles. Abundant experimental data have shown that multi-walled carbon nanotubes (MWNTs) are toxic to plants, but the potential impacts of exposure remain unclear. The objective of the present study was to evaluate possible phytotoxicity of MWNTs at 0, 20, 200, 1000, and 2000 mg/L with red spinach, lettuce, rice, cucumber, chili, lady's finger, and soybean, based on root and shoot growth, cell death, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 60 publications
3
34
0
2
Order By: Relevance
“…Watersoluble MWCNT (wsMWCNT) had a significant effect on the growth of Cicer arietinum L. plants (Tripathi et al 2011). The germination rate of corn and rye plants treated with MWCNT was reduced, while the root length was increased (Begum et al 2012(Begum et al , 2014. In the present study, in the concentration of 2 µg · ml the germination percentage increased, quite similar to the control, and the radicle length, in comparison with the control, increased as well.…”
Section: Discussionsupporting
confidence: 63%
“…Watersoluble MWCNT (wsMWCNT) had a significant effect on the growth of Cicer arietinum L. plants (Tripathi et al 2011). The germination rate of corn and rye plants treated with MWCNT was reduced, while the root length was increased (Begum et al 2012(Begum et al , 2014. In the present study, in the concentration of 2 µg · ml the germination percentage increased, quite similar to the control, and the radicle length, in comparison with the control, increased as well.…”
Section: Discussionsupporting
confidence: 63%
“…Bên cạnh những tác động tích cực, cũng có những thông báo cho thấy việc sử dụng các chế phẩm nano kích thích tăng trưởng hoặc làm phân bón lá với nồng độ cao có thể để lại tồn dư trong đất, gây ô nhiễm cho đất trồng sau nhiều vụ gieo trồng (Theng Yuan, 2008;Rico et al, 2011;Begum et al, 2014). Tuy nhiên, việc sử dụng các hạt siêu phân tán có kích thước nano với liều lượng thấp để kích thích hạt giống trước khi gieo giúp cây trồng phát triển khỏe mạnh, tăng năng suất và không tồn tại dư lượng các hạt nano trong nông sản hay trong đất trồng (Churilov et al, 2012;Ngo et al, 2013Ngo et al, , 2014.…”
Section: Mở đầUunclassified
“…Nowadays, nanomaterials have been wildly used in agriculture as fertilizers, growth regulators, plant protection agents to stimulate crop productivities due to their particularly small size and unique properties (Roduner, 2006;Adhikari et al, 2010). A number of studies focused on the effectiveness and safety of using metal nanoparticles in agriculture production (Alloway, 2008;Sheykhbaglou et al, 2010;Rico et al, 2011;Kole et al, 2013;Begum et al, 2014). Among the micronutritinal elements required for normal plant development, manganese (Mn), copper (Cu), iron (Fe), zinc (Zn), boron (Bo), chlorine (Cl), molybdenum (Mo), and cobalt (Co) are essential for the growth of plants (Alloway, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are also several studies to evaluate the undesirable effects of nanomaterials on plants and indicated that the majority of nanoparticles were beneficial or have no significant effect on plant growth; adversely effects on certain crops were reported in limited casses (Rico et al, 2011;Begum et al, 2014). When evaluating the possible toxicity of the five nanoparticles, Lin & Xing (2007) found that only Zn and ZnO nanoparticles inhibited germination and root development in six plant species.…”
Section: Introductionmentioning
confidence: 99%